Invigilator scheduling for faculty final examination - Teo, Mei Gie (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study concerns with the invigilator scheduling problem at faculty. For this, both the hard and soft constraints considered are clearly defined. The main hard constraint is invigilator can only invigilate one exam at a time. Besides, the soft constraint is evenly spread of invigilation duties among the staffs. The problem is formulated as a zero-one integer linear programming in which its variables correspond to the assignment decision are representative by binary integer, 0 and 1. Hardly any mathematical models have been used in the past since the problem has its own constraints and multiple objective structures. Therefore, simple heuristic approaches are used to assign invigilator to examination rooms.